Indigenous Cabildos and Constitutional Ayuntamientos: Local Governance in the villages of Chiapas during the Centralist Period, 1836-1855 (2024)
In the aftermath of independence, indigenous local authorities and governments continued to play a significant role in the daily lives of the villages, particularly during periods of centralized rule. This study delves into the collection of taxes, a crucial component of state finance, which was the responsibility of the ayuntamientos (municipal councils). Under centralized national governments, whose policies were reflected in the state of Chiapas, these councils diminished in importance and number, leaving some towns without a centralized body to collect direct taxes and cápita (poll taxes). During these periods, the establishment of cabildos (indigenous councils) was authorized in areas where it was deemed necessary.This authorization was motivated by the need to expedite tax collection. This development presented an opportunity for indigenous authorities, who had long been involved in tribute collection, to continue managing the affairs of their communities.